Faded Fonts - Aparna Sundar; Ruomeng Wu; Frank R. Kardes (Interdisciplinary Journal of Signage and Wayfinding, 2019)
Faded fonts on billboards and signage causes awareness of missing information. In this research, we highlight the importance of fonts in advertising and wayfinding and how it impacts sensitivity to missing information. Across two studies, we demonstrate that disfluency caused by faded fonts can reduce omission neglect. Study 1 establishes the basis for consequences of disfluency on omission neglect as well as its effects on judgments. Study 2 demonstrates that disfluency increases awareness of missing information by reducing response time differences for correctly identifying previously presented versus missing information. Taken together, the two studies demonstrate that disfluency increases sensitivity to absent information. Practical implications to signage and theoretical contributions to research on omission neglect are discussed.